Data mining of baskets collected at different locations over one year - Mladenić, Dunja (Informatica (Ljubljana), 2001)
This paper describes the first steps in analysis of millions of baskets collected over the past year from a retail grocery chain containing hundreds of stores. Each record in the data set represents an individual item processed by an individual checkout laser scanner at a particular store at a particular time on a particular day. In order to get some insights in the data, we used several different approaches including some statistical analysis, some machine learning, and some data mining methods. The sheer size of the data set has forces us to go beyond usual data mining methods and utilize Meta-Mining: the post processing of the results of basic analysis methods.
Keywords: računalniško programiranje; podatkovno rudarjenje; odločitvena drevesa; umetna inteligenca